Lean manufacturing implementation in regions with scarce resources: A survey in the Amazon Region of Brazil. Issue 2 (16th December 2019) - Negrão, Léony Luis Lopes; Godinho Filho, Moacir; Ganga, Gilberto Miller Devós; Chopra, Sunil; Thürer, Matthias; Sacomano Neto, Mário; Marodin, Giuliano Almeida
Abstract : Purpose: The purpose of this paper is to explore the adoption of lean practices by manufacturing companies in regions of low economic and technological development and to compare findings with previous studies from more developed regions highlighting important contextual differences. The paper uses the contingency theory to explore how contextual variables and scarce resources influence the adoption of lean practices. Design/methodology/approach: A survey of 233 manufacturing firms was conducted in the State of Pará in the Amazon Region of Brazil. Findings: The results demonstrate that six internal lean practices (single minute exchange of dies, human resource management, continuous flow, total productive maintenance, pull and statistical process control) and two external lean practices (supplier feedback and customer involvement) are implemented. However, the two external lean practices of just-in-time delivery by suppliers and supplier development were not implemented. Furthermore, from the 36 operating items comprised in eight lean practices that are being used, 13 were not implemented. As such, compared to developed regions, there is evidence for a more fragmented implementation in less developed regions. The results reveal empirical evidence explained by the contingency perspective, such as national, geographical, strategic context and culture. Originality/value: There is broad evidence on lean implementation in developed and developing countries in the literature. However, little is known about lean implementation in poorer regions of developing counties. This is one of the first studies mapping lean implementation in a region with low economic and technological development. This has important implications for research and practice, especially to cross-country/cultural research on operation management.